(untitled) (Mustansiria Dental Journal, 2018)
Background :This study was conducted to evaluate the effect of yogurt on the surface microhardness of two types of composite resins; (Filtek™ P90 Low Shrink Posterior Restorative, 3M ESPE,USA), and (Filtek™ Z350 Posterior Restorative, 3M ESPE,USA). Forty samples of composite were prepared by using cylindrical mold (2mm in hight and 8mm in diameter )..All specimens were stored in plastic container that contain distilled water and incubated 37cº for 24 hours before they were tested. twenty samples of each type of composite were divided into two groups (10) for each , baseline measurements for surface microhardness test was taken for all composite samples using the micromet microhardness tester (Vichers hardness tester) with a l00g load was applied for 15 seconds in which three indentations were made for each sample and converted into Vickers Hardness Number (VHN ) .After baseline measurement 10 samples of each type of composite were alternately immersed manually by holding the specimen by a pair of tweezers from its sides, , in drinking yogurt (Activia ,KSA) and artificial saliva for 10 cycles 5 seconds each at room temperature (25cº). This was repeated three times a day (8am,4pm,12am) at 8hours intervals for one week. the other 10 samples for each type of composite were immersed in artificial saliva only. The total soaking time in both drinking yogurt and saliva was 100 seconds. After the soaking sequence was completed the specimen was rinsed with distilled water and subjected to surface microhardness test (Vichers hardness tester). Descriptive statistics(mean values and standard deviations with the minimum and maximum values and Statistical analysis of data by using student t - test for all groups was carried out between the means of each type of composites ,the results showed a significant reduction in VHN values (at P<0.05)of Filtek™ Z350 Posterior Restorative composites after immersion in artificial saliva, while the (Filtek™ Z350 Posterior Restorative, 3M ESPE) composite showed a highly significant reduction in VHN values (at P<0.01)after immersion in drinking yogurt. Filtek™ P90 Low Shrink Posterior Restorative composites showed a non significant reduction in VHN values (at P>0.05) after immersion in artificial saliva and after immersion in drinking yogurt. Filtek™ P90 Low Shrink Posterior Restorative composites have highest VHN value than Filtek™ Z350 Posterior Restorative composites, and surface microhardness results showed that drinking yogurt highly significantly effect on the Filtek™ Z350 Posterior Restorative composites while it has non significant effect on the Filtek™ P90 Low Shrink Posterior Restorative composite